The exploratory and Confirmatory Factorial structure for Riso-Hadson enneagram test indicator (Journal Of Educational and Psychological Researches, 2016)
This  investigation was conducted to recognize the structure for (RHETI version 2.5  1999) by using exploratory and confirmatory factor analysis. Sample of (620) student of Al-Mustansrya University were administered the (RHETI).The data of their responses was analyzed by using (PAF) and oblique rotating .The findings explored (9) factors as one factor for each type and (184) items were loaded by the factors: (60) item for feeling center, (61) items for instinctive center and (63) items for thinking center.Results of confirmatory factorial analysis supported a model designed by the researcher depended upon a theoretical views of Riso and Hudson.